Britain's promise to forget: some historiographical reflections on What Do Students Know and Understand about the Holocaust?. Issue 3 (3rd July 2017) - Lawson, Tom
ABSTRACT: This article is a personal reflection on the report produced by the UCL Centre for Holocaust Education, What Do Students Know and Understand about the Holocaust? It reviews the report's findings and reflects upon the gap between scholarly debates and public knowledge. It then attempts to account for this gap, especially in the light of the rhetoric surrounding Holocaust education and commemoration in the UK and the "need to remember." Ultimately it argues that the ignorance and misunderstanding highlighted in the report have come about as a consequence of, rather than in spite of, the dominant culture of Holocaust remembrance in the United Kingdom.